2022
DOI: 10.3389/fendo.2022.904089
|View full text |Cite
|
Sign up to set email alerts
|

Letrozole Supplementation and the Increased Risk of Elevated Progesterone Levels on Trigger Day

Abstract: Although using letrozole (LE) during in vitro fertilisation and intracytoplasmic sperm injection (IVF/ICSI) has many advantages, it remains unclear whether LE induces an increase in progestogen during the late follicular phase. The objective of this study was to investigate whether progesterone levels increased under antagonist protocols supplemented with LE on the trigger day using a retrospective cohort study. The study included 1,133 women who underwent IVF/ICSI cycles from January 2018 to June 2020. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A retrospective cohort study has revealed that the live birth rate was significantly lower in CC cycles compared to that with natural cycles ( p = 0.01), whose underlying mechanism might be that CC influenced uterine receptivity by reducing endometrial thickness through antiestrogenic effects ( 16 ). Besides, the use of LE during inducing ovulation has been reported to be correlated with a notable risk of elevating progesterone levels, which has an adverse effect on the pregnancy rate ( 17 ). Hence, over the past few years, an alternative approach known as progestin-primed ovarian stimulation (PPOS) in controlling the LH surge has attracted lots of clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective cohort study has revealed that the live birth rate was significantly lower in CC cycles compared to that with natural cycles ( p = 0.01), whose underlying mechanism might be that CC influenced uterine receptivity by reducing endometrial thickness through antiestrogenic effects ( 16 ). Besides, the use of LE during inducing ovulation has been reported to be correlated with a notable risk of elevating progesterone levels, which has an adverse effect on the pregnancy rate ( 17 ). Hence, over the past few years, an alternative approach known as progestin-primed ovarian stimulation (PPOS) in controlling the LH surge has attracted lots of clinicians.…”
Section: Introductionmentioning
confidence: 99%